Flex, adapt, and engage: A new framework for EFL teaching success - Yunus, Muhammad; Anggraini, Riesty Kartika; Romadhon, M Galuh Elga (Journal of Research on English and Language Learning (J-REaLL), 2025)
Although the Independent Curriculum of Indonesia promotes self-directed learning and encourages the active involvement of learners, minimal student participation continues to be a persistent challenge. Prior research has reductively viewed student engagement as simply attendance, and few have looked at how teachers fill this gap within the flexible structure of the curriculum. This qualitative case study tries to fill this gap by looking at one East Java English teacher's experiences through narrative interviews. Findings illuminate her multifaceted strategies such as energizing students and encouraging the use of English, adapting lessons in real-time, and implementing a multitude of methods. Persistent challenges included high rates of absenteeism and a general reluctance to converse in English. These indicate a greater need for tailored approaches and ongoing, differentiated instructional support from teachers to meet the aims of the curriculum. Due to the analysis consisting of only one single participant, the findings may not be generalizable; however, the results provide direct insight for educators regarding changes to instructional strategies as well as for policy makers in developing policies grounded on research. Subsequent inquiries should increase participant numbers and integrate other forms of documentation to build evidentiary strength. Such efforts can inform responsive approaches to foster language acquisition in Indonesia and comparable settings.